A. Acosta y U. Brand. Salidas del laberinto capitalista. Decrecimiento y postextractivismo. Barcelona: Editorial Icaria. 2017 - Gómez-Castillo, Harvey; Jaramillo Villamizar, Oswaldo (Visión electrónica, 2019)
A. Acosta y U. Brand. Salidas del laberinto capitalista. Decrecimiento y postextractivismo. Barcelona: Editorial Icaria. 2017 US